2018
DOI: 10.1021/acs.biomac.8b01328
|View full text |Cite
|
Sign up to set email alerts
|

DNA–Polymer Conjugates by Photoinduced RAFT Polymerization

Abstract: Conventional grafting-to approaches to DNA-polymer conjugates are often limited by low reaction yields due to the sterically hindered coupling of a pre-synthesized polymer to DNA. The grafting-from strategy, in contrast, allows to directly graft polymers from an initiator that is covalently attached to DNA. Herein, we report blue light-mediated reversible additionfragmentation chain-transfer (Photo-RAFT) polymerization from two different RAFT agentterminated DNA sequences using Eosin Y as the photocatalyst in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 76 publications
0
65
0
3
Order By: Relevance
“…26,27 Kong and co-workers have proposed various kinds of electrochemical sensor based on RAFT polymerization or ATRP polymerization for detection of sequence-specific DNAs and suggested that RAFT has better bio-compatibility as transition-metal, Cu 2+ of ATRP can cause toxicity. 28,29 Because RAFT polymerization is harmless to biomolecules 30 , it has great application prospects as a simple and effective signal amplification technique for biosensing for biomolecule detection. However, fluorescence detection DNA based on RAFT polymerization signal amplification has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Kong and co-workers have proposed various kinds of electrochemical sensor based on RAFT polymerization or ATRP polymerization for detection of sequence-specific DNAs and suggested that RAFT has better bio-compatibility as transition-metal, Cu 2+ of ATRP can cause toxicity. 28,29 Because RAFT polymerization is harmless to biomolecules 30 , it has great application prospects as a simple and effective signal amplification technique for biosensing for biomolecule detection. However, fluorescence detection DNA based on RAFT polymerization signal amplification has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, while the first solution-based RAFT polymerization from DNA was successful, it had to still rely on conventional degassing, which limited its robustness. [20] Thus, we applied enzyme degassing as a significant progress for transferring polymerization processes to ultralow volumes and low radical concentrations. [21,22] In this way, the access to DNA-diblock copolymers of the type DNA-A-B (A and B denote different synthetic polymer units), as well as random DNA copolymers was made possible (Figure 1).…”
mentioning
confidence: 99%
“…[4] Echoing these developments,awide range of controlled photopolymerizations regulated by visible wavelengths have been developed, [5] creating new opportunities in the preparation of functional materials. [6] Although visible-and UVlight-mediated polymerizations are now well established, [7] there have been very few examples utilizing far-red or near infra-red (NIR) light due to their lower energy. [8] The enhanced penetration of non-transparent materials by these wavelengths are promising for the development of new and exciting applications.…”
mentioning
confidence: 99%